PEMAHAMAN DAN KETERAMPILAN KERJA MAHASISWA SETELAH MENGIKUTI PRAKTIK KERJA DI BANK SYARIAH - Muhammad Imran; Ummi Kalsum; Sailan Sailan; Muh Sajjaj Sudirman (Institut Agama Islam Negeri (IAIN) Ternate, 2022)
This reserch aims to find 1) Does the practical experience in the field can improve students' understanding related to their work in Islamic banking? 2) Does the field practice experience can improve student work skills in Islamic banking? This research uses a qualitative method with a descriptive approach. Primary and secondary data were gathered for this study through observation, interviews, and documentation. The researches sample consisted of 9 Islamic banking students from the FEBI IAIN Kendari class of 2016/2017 who took part in the second batch of field experience practice. The research's descriptive methods include data reduction, data visualization, and conclusion-making. The results of the study demonstrate that the knowledge of the class of 2016/2017 students studying Islamic banking has greatly improved after they began taking part in Field Experience Practice (PPL 2) activities as opposed to earlier, when they solely learnt from lectures. Increasing knowledge and proficiency of working mechanisms also improves job skills.Keywords: Work Understanding; Work Skills; Practical Field Exprience